Safe leg surgery: the anatomic principles and techniques - S. V., Akshay Kumar; S., Venkatesh Babu (International Surgery Journal, 2020)
The goals of surgical treatment of leg injury are to achieve soft tissue healing, good osseous union and to restore the length of the limb, correct alignment of both bones with their respective joints and normal range of movements of the entire limb at the earliest. Presently, the surgical treatment has been standardised for the tibia fractures for adults and children. Though the surgical progress made in the implants, instruments and techniques, there are considerable surgical complications happening. This article highlights the need of anatomical expertise and safe operative ability for the surgeon.